Influence of IGF-I and IGFBP-3 on bone mineral density in postmenopausal women - Skowrońska-Jóźwiak, Elżbieta; Lewiński, Andrzej (Menopause Review/Przegląd Menopauzalny, 2006)
Aim of study: Serum concentration of insulin-like growth factor-I (IGF-I) decreases with age but the link between IGF-I and postmenopausal osteoporosis remains controversial. IGFBP-3 is IGF-I binding protein, which prolongs the half-life of IGF-I and serves as metabolic reservoir of IGF-I. The goal of this study was to determine the effect of IGF-I and IGFBP-3 on bone mineral density in postmenopausal women. Materials and methods: The study included sixty-two (62) postmenopausal women, mean age 69.8±8.3 years. All the women were examined in order to exclude any other risk factors of osteoporosis. Results: Bone mineral density (BMD) was measured in the femoral neck, using dual-energy X-ray absorptiometry (DPX, Lunar, USA). The obtained results were evaluated vs. WHO criteria of osteoporosis. IGF-I and IGFBP-3 were measured by RIA (IGF-I Biosource Europe S.A., Belgium; IGFBP-3 Immunotech, France). Serum concentrations of IGF-I and IGFBP-3 were significantly lower in the group of osteoporotic women and correlated positively with BMD of the femoral neck, respectively (r=0.48, p<0.001 and r=0.43, p<0.001). Conclusions: Our study indicates that low concentrations of IGF-I and of its binding protein (IGFBP-3) in postmenopausal women may be responsible for the loss of bone mineral density, thus leading to osteoporosis development.